Efficacy and Safety of YJP-40 in Patients with Acute Bronchitis: A Randomized, Double-Blind, Parallel Group Study - Chin Kook Rhee (Tuberculosis and Respiratory Diseases, 2025)
Background Pelargonium sidoides has been known to be effective in treating respiratory diseases. P. sidoides extract (Umckamin®, Han Wha Pharmaceuticals) was approved in Korea for acute bronchitis. YJP-40 (Umckamin plus®) is formulated with extract of P. sidoides and ivy leaf. Ivy leaf extract has an expectorant effect and has been used to treat bronchitis. The aim of this study was to compare the efficacy of YJP-40 syrup with Umckamin® syrup in patients with acute bronchitis. Methods This was a multicenter, randomized, double-blind, active-controlled, non-inferiority, phase III clinical trial. Patients were randomized 1:1 to either the test (YJP-40) or the control (Umckamin®) group. The primary endpoint was the change in bronchitis severity score (BSS) total score 7 days after administration. Results A total of 240 subjects (test group 121; control group 119) from seven hospitals were enrolled in this clinical trial. The average change in BSS total score 7 days after administration compared to before was –4.31±2.09 and –4.36±1.71 in the test group and the control group, respectively. The non-inferiority of the test group to the control group was demonstrated. The response rate at 7 days after administration was 87.16% (95/109) in the test group and 86.92% (93/107) in the control group (p=0.9778). There was no statistically significant difference between the groups in the incidence of adverse events. Conclusion YJP-40 can be a safe and effective treatment option for acute bronchitis.